2021
DOI: 10.1021/acs.langmuir.1c02298
|View full text |Cite
|
Sign up to set email alerts
|

pH and Temperature Double-Switch Hybrid Micelles for Controllable Drug Release

Abstract: pH/temperature dual-responsive hybrid micelles were prepared for constructing a double-locked drug delivery system. The temperature-sensitive polyethylene glycol−poly-(tetrahydropyranylmethacrylate)−polyethylene glycol (PEG− PTHPMA−PEG) triblock copolymers were synthesized by reversible addition−fragmentation chain transfer polymerization and amide coupling reaction. pH-sensitive poly(2-(diisopropylamino ethylmethacrylate)−polyethylene glycol (PDPA−PEG) diblock polymers were introduced, which could self-assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…We used the reconstitution approach with synthetic systems. Reconstitution approach is advantageous in the sense that researchers can test physical models in a well-defined environment that can inspire them to design and synthesize biomimetic systems for therapeutic purposes. In this study, we used bottom-up reconstitution with giant unilamellar vesicle (GUV) system, a lipid bilayer vesicle with a typical diameter of 1–100 μm. GUV has a relatively well-defined lipid composition and can be readily observed by optical microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…We used the reconstitution approach with synthetic systems. Reconstitution approach is advantageous in the sense that researchers can test physical models in a well-defined environment that can inspire them to design and synthesize biomimetic systems for therapeutic purposes. In this study, we used bottom-up reconstitution with giant unilamellar vesicle (GUV) system, a lipid bilayer vesicle with a typical diameter of 1–100 μm. GUV has a relatively well-defined lipid composition and can be readily observed by optical microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-drug delivery system has been demonstrated to be a useful strategy for improving the therapeutic effect of anticancer drugs and reducing their side effects due to the existence of enhanced permeability and retention effect in tumor tissues. , Among them, nano-polymeric micelles assembled from amphiphilic polymers have shown unique advantages in enhancing the solubility of hydrophobic anticancer drugs and being easy to functionalize. …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, nanocarrier-based drug delivery systems have been spotlighted in last several decades due to their superiority in drug targeting issues [ 17 , 18 , 19 , 20 , 21 ]. Due to their small size, nanocarriers are believed to be an ideal candidate for tumor targeting [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the surface of nanocarriers such as polymeric nanoparticles can be easily decorated with targeting moieties such as monoclonal antibodies, they can then be specifically delivered to the tumor with a minimization of side effects against normal cells [ 17 , 18 ]. Furthermore, nanocarriers based on polymeric nanoparticles or micelles can be designed to stimulate of tumor tissues and then deliver the anticancer drug to the tumor tissues specifically [ 18 , 19 , 20 , 21 ]. For example, Lei et al reported that polymeric micelles having pH and temperature dual-responsive properties accelerate the release rate of anticancer drugs at an acidic pH and a higher temperature [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation